Predicting Vertebral Bone Strength Using Finite Element Analysis for Opportunistic Osteoporosis Screening in Routine Multidetector Computed Tomography Scans—A Feasibility Study - Rayudu, Nithin Manohar; Dieckmeyer, Michael; Löffler, Maximilian T.; Noël, Peter B.; Kirschke, Jan S.; Baum, Thomas; Subburaj, Karupppasamy (Frontiers in Endocrinology, 2021)
PURPOSE: To investigate the feasibility of using routine clinical multidetector computed tomography (MDCT) scans for conducting finite element (FE) analysis to predict vertebral bone strength for opportunistic osteoporosis screening. METHODS: Routine abdominal MDCT with and without intravenous contrast medium (IVCM) of 7 subjects (5 male; 2 female; mean age: 71.86±7.40 years) without any bone disease were used. FE analysis was performed on individual vertebrae (T11, T12, L1, and L2) including the posterior elements to investigate the effect of IVCM and slice thickness (1 and 3 mm) on vertebral bone strength. Another subset of data from healthy and fracture subjects (n = 9 age and gender-matched pairs) was analyzed for investigating the ability of FE-analysis to differentiate healthy vs. osteoporotic fracture cohorts. Bland-Altman plots, box plots, and coefficient of correlation (R2) were calculated to determine the variations in FE-predicted failure loads for different conditions. RESULTS: The FE-predicted failure loads obtained from routine MDCT scans were strongly correlated with those from without IVCM (R2 =0.91 for 1mm; R2 = 0.92 for 3mm slice thickness, respectively) and different slice thicknesses (R2 = 0.93 for 1mm vs. 3mm with IVCM). Furthermore, a good correlation was observed for 3mm slice thickness with IVCM vs. 1mm without IVCM (R2 = 0.87). Significant difference between FE-predicted failure loads of healthy and fractured patients was observed (4705±1238 vs. 4010±1297 N; p=0.026). CONCLUSION: Routine clinical MDCT scans could be reliably used for assessment of fracture risk based on FE analysis and may be beneficial for patients who are at increased risk for osteoporotic fractures.